Content Richness, Perceived Price, and Perceived Ease of Use in Relation to the Satisfaction Level and Brand Equity in Streaming Platforms - Dextre-Mamani, Romina (2022)
Streaming platforms have become popular in recent years, where consumers can view personalized content at any time on the device of their choice. Many brands in this market have been fighting to win more market share. It was seen how they improved their strategies based on several factors such as price, ease of use, content richness, or brand equity. Users tend to have high satisfaction with the streaming platform depending on what brand offers what they value the most. The objective of this study was to find the relationships that the variables content richness (CR), perceived price (PR), perceived ease of use (PEOU), brand equity (BE), and user satisfaction (US) have within this market. The study population was made up of subscribers of streaming platforms in Peru, in which the sample was 400 subscribers who used streaming platforms for more than 6 months. The methodology used was a PLS-SEM analysis using the SmartPLS 3 tool to answer the hypotheses raised in the study. All the scale items were measured by a 7-point Likert scale. The results from the investigation indicated that brand equity was significantly influenced by both content richness and perceived ease of use. Moreover, brand equity and user satisfaction have a high significance between them. This may be since users now value more the richness of content and ease of use on streaming platforms. However, the perceived price was not significantly predictive of brand equity, it could be because some streaming platforms offer more than one pricing plan and the perceptions disperse even more than with the other variables. Overall findings suggest reinforcing the relationships between CR and BE, since there have not been previous investigations.